Charles Wright Mills’ Concept of "The Power Elite" Triangle According to the Georgian Model of 1990-2020 - Gamzardia, Archil (European Scientific Journal, ESJ, 2023)
The paper presents similarities and differences of Charles Wright Mills’s concept of "The Power Elite" triangle on the Georgian model of 1990-2020. The article presents a research on the Georgian analogue of the Mills concept in the context of church power, army and, in general, force power, economic and financial elites. It is also about the promotion of the bourgeoisie in the American society and the factors of developed skills, which essentially differentiates the American existence from the Georgian existence. In the article, I discuss the conditions, which represent The Mills concept, on the example of Georgia, how the factor of church power differs, which in our case plays the role of essential influencing power, what was the condition of the rulers of Georgia over the years against the background of the confrontation between secular and clerical power elites, and what is the overall result we got today. The article provides a qualification that is derived from research and analysis. The article explains why financially powerful groups and individuals in political and governmental layers are getting stronger in Georgia, why citizens do not have the appropriate conditions for influence, what factors prevent the strengthening of civic influence in Georgia. In some cases, the Mills constructions, like the example of Georgia, even look paradoxical, declaring that the state is one, while creating a radically different reality and trend. The article studies the influence of the Apostolic Autocephalous Orthodox Church of Georgia on maintaining power in Georgia and its characteristics. There are highlighted Mills views about democracy resources, context and content comparability, the factors impacting the bourgeoisie in the development and strengthening democracy, that is represented quite differently in Georgian model. The article discovers the theoretic factors that hinders the development of democratic values in Georgia - the historical and modern contexts of aristocracy and feudalism, superiority of church hierarchy in maintaining power, secular authorities longing for authoritarianism and mutual subordination of secular and clerical power elites with the weird synthesis of partnership.